2015
DOI: 10.1038/jhg.2015.64
|View full text |Cite
|
Sign up to set email alerts
|

Functional and genetic diversity of leukocyte immunoglobulin-like receptor and implication for disease associations

Abstract: Human leukocyte immunoglobulin-like receptors (LILR) are a family of 11 functional genes encoding five activating (LILRA1, 2, 4-6), five inhibitory (LILRB1-5) and one soluble (LILRA3) form. The number of LILR genes is conserved among individuals, except for LILRA3 and LILRA6, which exhibit copy-number variations. The LILR genes are rapidly evolving and showing large interspecies differences, making it difficult to analyze the functions of LILR using an animal model. LILRs are expressed on various cells such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 81 publications
(89 reference statements)
2
86
0
1
Order By: Relevance
“…1E, the Zika virus-induced upregulation of MHC class I expression resulted in increased binding of KIR2DL2 Ig, which binds HLA-C proteins carrying asparagine at position 80 (49), and LILRB1 Ig, which interacts with HLA-A, -B, and -C proteins (50).…”
Section: Resultsmentioning
confidence: 99%
“…1E, the Zika virus-induced upregulation of MHC class I expression resulted in increased binding of KIR2DL2 Ig, which binds HLA-C proteins carrying asparagine at position 80 (49), and LILRB1 Ig, which interacts with HLA-A, -B, and -C proteins (50).…”
Section: Resultsmentioning
confidence: 99%
“…Although LILR interactions with classical class I has been extensively examined in terms of class I variation, the reciprocal examining diversity of LILRs binding to MHC-I has only been tested in one case in which a link between polymorphism in LILRB1 and rheumatoid arthritis showed that alterations in expression levels and not binding were involved (25). However, LILR genetic diversity and/or altered expression is quite possibly involved with autoimmune disease or changes in the response to infection, and this has been reviewed elsewhere recently (33).…”
Section: Nonconventional Mhc-i Ligandsmentioning
confidence: 99%
“…Although counterintuitive, the direct tumor-supportive roles of LILRBs are consistent with the generally immune-suppressive and thus tumor-promoting functions of the inhibitory receptors in the immune system [45]. The roles of LILRBs in immune and neuronal diseases have been recently reviewed [2,4,46,47]. Here we will focus on the ligands, expression pattern, signaling, and the immune-modulatory and direct tumor-supportive roles of LILRBs in cancer development.…”
Section: Introduction To Itim-containing Receptors and Lilrbsmentioning
confidence: 99%